Effect of an artificial Ascaridia galli infection on egg production, immune response, and liver lipid reserve of free-range laying hens. (13th December 2017) - Sharma, N; Hunt, P W; Hine, B C; McNally, J; Sharma, N K; Iqbal, Z; Normant, C; Andronicos, N M; Swick, R A; Ruhnke, I
Abstract: This study was conducted to determine the effect of Ascaridia galli infection on free-range laying hens. Lohmann Brown laying hens (n = 200) at 17 wk of age were allocated to 4 treatment groups (n = 50 per group), each with 5 replicate pens of 10 hens. Hens in 3 treatment groups were orally inoculated with different doses of embryonated A. galli eggs: low (250 eggs), medium (1, 000 eggs), and high (2, 500 eggs) levels, whereas hens of the control group were not infected. Infection levels were monitored using excreta egg counts and mature A. galli worm counts in the intestine. Anti A. galli antibody titers (IgY) in the serum were measured prior to infection, and at 6, 11, 15, and 20 wk post infection (PI) and in egg yolk at 11 and 20 wk PI. Parameters evaluated included feed intake, egg production, egg weight, egg mass, FCR, liver weight, liver fat, and intra epithelial immune cell infiltration. The results showed no difference in feed intake, body weight, or FCR among any treatment groups ( P  > 0.05). Egg production was lower in the low infection group compared to other groups at 20 wk of age ( P  < 0.01). Serum IgY was higher in the infected groups' hens at 20 wk PI compared to control group hens ( P  < 0.01). Yolk IgY increased significantly over time and was higher in infected hens compared to hens of the control group at 11 and 20 wk PI ( P  < 0.001). No differences were observed in liver lipid content or intraepithelial lymphocytes infiltration among treatment groups. Ascaridia galli eggs in the coprodeum content and adult A. galli worm count were higher in infected hens compared to hens of the control group ( P  < 0.01). In conclusion, the effects of artificial infection with A. galli on the parameters investigated were minor, and egg yolk antibody may be a more reliable indicator of A. galli infection than serum antibody or excreta egg count.